Pharmacokinetics, tissue residues of tilmicosin phosphate (tilmicor-al®) and its in vitro and in vivo evaluation for the control of Mycoplas-ma gallisepticum infection in broiler chickens - Elbadawy, Mohamed; Aboubakr, Mohamed (International Journal of Pharmacology and Toxicology, 2017)
The aim of present study was to determine the pharmacokinetics and tissue residues of tilmicosin phosphate (tilmicoral®) as well as its in vitro and in vivo evaluation for control of Mycoplasma gallisepticum (MG) infection in broiler chickens. Pharmacokinetics (single oral dose) and tissues residues (daily for five days) of tilmicosin (25 mg/kg b.wt) in broilers were investigated. Peak plasma concentration of tilmicosin was 1.25±0.0.09 μg/mL and achieved at 3.15±0.34 h. Elimination half-life was long (44.3±7.22 h) and Vdarea was large (1.25±0.082 L/kg). Residue study revealed a good distribution and penetration of tilmicosine in lung, liver, kidney and muscles. Tilmicosin could not be detected in all tested tissues (except in lung) at 6 days after last administration. The MIC of tilmicosin and tylosin against MG were 0.054 and 0.319 μg/mL, respectively. MG infected chickens and treated by tilmicosin or tylosin showed a significant (p<0.05) improvement in mean body weights gain and a significant (p<0.05) decline in mean clinical signs score, air sac lesion score and mortality rate, however tilmicosin was a superior drug. In conclusion, timicoral® was a very effective medication for controlling MG infection in broiler chickens due to its rapid absorption, long elimination half-life, rapid and extensive penetration from blood into tissues especially lungs and air sacs. Additionally, tilmicoral® had a short withdrawal time. Moreover, its superior efficacy (in vitro and in vivo) against MG.